2020
DOI: 10.1111/josh.12863
|View full text |Cite
|
Sign up to set email alerts
|

School Climate as an Intervention to Reduce Academic Failure and Educate the Whole Child: A Longitudinal Study

Abstract: BACKGROUND: Preventing student academic failure is crucial to student health and life success. Previous studies suggest a positive school climate may reduce students' risk for academic failure and contribute to academic success. The purpose of this study was to determine the longitudinal associations between school climate and academic grades in a group of middle school students who transition into high school. METHODS:Parallel latent growth curve modeling was used to examine changes among study variables long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 86 publications
(97 reference statements)
0
15
0
4
Order By: Relevance
“…As research on school environment and climate shows, learning in a safe and supportive environment free of violence is essential for children's academic success, self-esteem, and wellbeing [2][3][4][5]. Developing positive feelings, such as friendship and empathy, is essential for ensuring such spaces in schools and classrooms [8,13,18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As research on school environment and climate shows, learning in a safe and supportive environment free of violence is essential for children's academic success, self-esteem, and wellbeing [2][3][4][5]. Developing positive feelings, such as friendship and empathy, is essential for ensuring such spaces in schools and classrooms [8,13,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Learning in inclusive, violence-free, and supportive environments has been found to foster students' positive trajectories. For instance, such environments contribute to improving students' self-esteem and self-concept [2], academic achievements [3], academic engagement [4], and social and emotional wellbeing [5], among others. It has been found that the quality of relationships and interactions within and outside the school among students, parents, and teachers is one of the main pillars in school environments promoting a positive climate [6,7].…”
Section: Fostering Supportive and Safe Educational Environmentsmentioning
confidence: 99%
“…(p. 5) The United States Department of Education's (USDOE) Safe and Supportive Schools model presents positive school climate including 3 core domains: safety, engagement, and environment 2 . Research shows consistent associations between these aspects of school climate and students' mental, behavioral, and academic outcomes, 3‐7 highlighting the importance of fostering positive school climate for student well‐being. Yet, less is known about how broader context may moderate the experience and potential impact of school climate.…”
Section: The Rural School Contextmentioning
confidence: 98%
“…This is not only disheartening for the individual, but also a brain drain on communities, impacting the economy and wellbeing of families, communities and countries [31]. Education still needs to understand the need to teach all our children how to read and write, whilst at the same time addressing the need of access to learning without the use of the verbal visual [32,33].…”
Section: Literacy?mentioning
confidence: 99%